Formation of leadership qualities for future specialists in the economic profile by specialty 073 "management" in higher education institutions - Романовська, О. О. (Scientific notes of the pedagogical department, 2018)
The article is devoted to the consideration of such an actual problem as the formation of leadership qualities in future specialists of the economic profile - managers.The urgency of this problem in the work proves that domestic institutions of higher education should provide their graduates with such a level of training, which at the same time would allow them to continue education in any country of the European Union and would contribute to increasing competitiveness in the European labor market. In addition, it is noted that future heads of various institutions and organizations need not only broad general education but also developed leadership skills. The above is also reflected in public educational documents.Based on the analysis of scientific literature in the work noted that in order to get a manager who is able to act and respond to internal and external impulses that arise in the field of its activities, people need to form and develop, and not only technically prepare them. But only some of the higher education institutions create the conditions for the personal expression of future managers, the identification and development of the qualities that are necessary for the proper and effective management of any organization.The paper also states that the manager of the future is one who freely makes decisions and takes responsibility, shows leadership qualities, including a natural talent to motivate and convince his environment, and has the ability to prevent conflicts.The purpose of the article is to determine the level of leadership qualities of future managers as an example of a specific institution of higher education and to propose measures that promote the development and formation of leadership skills among students.An experimental study on leadership skills in UIРA student managers has revealed that the number of leaders is not large.According to the results, it was proposed to create a "School of Leader" with student self-government.Implementation of the "School of Leader" program involves classes in active form, aimed at increasing the potential and independence, development of communicative abilities and personal development of each participant. Increasing the chances of everyone becoming a true leader in his chosen field of activity and life, his ability to lead a team, and a sense of social responsibility - and should be the result of this program.